The Effect of Direct and Indirect Boiling on Chemical Composition and Microbial load of Disposed Waste Fish of White Nile State, Sudan - Salih, Ghanim E.; Alkhawad, Ibrahim E.; Babiker, Mutaz S.; Abdel-Rahim, Awad M. (Gezira Journal of Engineering and Applied Sciences, 2018)
The present study was conducted to evaluate the effect of direct and indirect boiling treatments on disposed fish collected from the White Nile River, South of Eldueim town, for the benefit of being used as local fishmeal. The fish samples were identified and analyzed microbiologically and chemically. Crude protein, fat, ash, and metabolizable energy values for treated and untreated samples were found higher than those of the imported broilers concentrates by 20%, 9.7%, 51%, and 36%, respectively. The levels of calcium for direct and indirect boiling treated and untreated samples were 5.6, 4.9, and 4.82%, while for phosphorus they were 3.49, 3.06, and 3.09%, respectively. Treated and untreated samples were higher in sodium content than that of the imported concentrate by 70%. They also one and a half times higher for the phosphorus content. The total concentrations of amino acids for direct and indirect boiling treated samples were 1.21 and 1.13% for methionine and 3.51 and 3.30% for lysine, respectively. Escherichia coli . was totally eradicated by treatments. The direct and indirect boiling gave large numbers of molds and Salmonella spp., amounting to 1.00 × 10 6 and 2.00 × 10 6 and 0.50 × 10 6 and 0.50 × 10 6 cfu/g, respectively. The results indicated that disposed fish could replace imported concentrates as feedstuff after direct and indirect boiling for poultry feeding, in Sudan.